Are heterozygous carriers for hereditary fructose intolerance predisposed to metabolic disturbances when exposed to fructose?. Issue 2 (27th June 2018) - Debray, François-Guillaume; Damjanovic, Katarina; Rosset, Robin; Mittaz-Crettol, Lauréane; Roux, Clothilde; Braissant, Olivier; Barbey, Frédéric; Bonafé, Luisa; De Bandt, Jean-Pascal; Tappy, Luc; Paquot, Nicolas; Tran, Christel
ABSTRACT: Background: High fructose intake causes hepatic insulin resistance and increases postprandial blood glucose, lactate, triglyceride, and uric acid concentrations. Uric acid may contribute to insulin resistance and dyslipidemia in the general population. In patients with hereditary fructose intolerance, fructose consumption is associated with acute hypoglycemia, renal tubular acidosis, and hyperuricemia. Objective: We investigated whether asymptomatic carriers for hereditary fructose intolerance (HFI) would have a higher sensitivity to adverse effects of fructose than would the general population. Design: Eight subjects heterozygous for HFI (hHFI; 4 men, 4 women) and 8 control subjects received a low-fructose diet for 7 d and on the eighth day ingested a test meal, calculated to provide 25% of the basal energy requirement, containing 13 C-labeled fructose (0.35 g/kg), glucose (0.35 g/kg), protein (0.21 g/kg), and lipid (0.22 g/kg). Glucose rate of appearance (GRa, calculated with [6, 6- 2 H2 ]glucose), fructose, net carbohydrate, and lipid oxidation, and plasma triglyceride, uric acid, and lactate concentrations were monitored over 6 h postprandially. Results: Postprandial GRa, fructose, net carbohydrate, and lipid oxidation, and plasma lactate and triglyceride concentrations were not significantly different between the 2 groups. Postprandial plasma uric acid increased by 7.2% compared with fasting values in hHFI subjects ( P < 0.01), but not in control subjects (−1.1%, ns). Conclusions: Heterozygous carriers of hereditary fructose intolerance had no significant alteration of postprandial fructose metabolism compared with control subjects. They did, however, show a postprandial increase in plasma uric acid concentration that was not observed in control subjects in responses to ingestion of a modest amount of fructose. This trial was registered at the US Clinical Trials Registry as NCT02979106.